The impact of the academy classification model on coaching practices in Norwegian football: a Foucauldian analysis of governance and player development. - Gagnås, H. L.; Thue Bjørndal, C. (Sports Coaching Review, 2025)
This study explores the impact of the Academy Classification Model (ACM) on coaching practices in Norwegian boys` football academies. Introduced in 2017, the ACM aims to standardise player development through structured criteria and data-driven assessments. Drawing on interviews with five academy managers and a Foucauldian lens, the study examines how the ACM operates as a technology of governmentality, shaping coaching through norms of standardisation, surveillance, and accountability. While the ACM supports professionalisation and institutional structure, it constrains coaching autonomy and promotes conformity by privileging measurable outcomes over contextual and relational aspects of practice. The dual role of ACM mentors - as both developmental supporters and compliance enforcers - exemplifies this tension. Biopolitical practices such as growth testing and workload monitoring further reduce development to quantifiable outputs. The findings call for governance models that balance accountability with pedagogical responsiveness, and support sustainable, context-sensitive, and relational approaches to coaching and talent development.